Blue light-induced phototoxicity in retinal cells: implications in age-related macular degeneration - Chakravarthy, Harshini; Georgyev, Vasil; Wagen, Cole; Hosseini, Amir; Matsubara, Joanne (Frontiers in Aging Neuroscience, 2024)
Sunlight exposure is recognized as a risk factor for the development of age-related macular degeneration (AMD), a common neurodegenerative retinal disease in the elderly. Specifically, the blue light wavelengths within sunlight can negatively impact the physiology of light-sensitive retinal cells, including retinal pigmented epithelium (RPE) and photoreceptors. This review explores blue light-induced retinal degeneration, emphasizing the structural and functional impairments in RPE. The initial section provides a brief overview of blue light’s effects on photoreceptors, followed by a comprehensive analysis of its detrimental impact on RPE. In vitro studies reveal that blue light exposure induces morphological alterations and functional impairments in RPE, including reduced phagocytic activity, disrupted secretion of neurotrophic factors, and compromised barrier function. Mechanisms of retinal damage, including oxidative stress, inflammation, lipofuscin accumulation, mitochondrial dysfunction and ER stress in RPE, are also explored. The strengths and limitations of in vitro, animal and ex vivo models for studying blue light exposure are discussed, with recommendations for improving reproducibility in future studies.